An investigation into the effects of bacterial fermentation in autism - Bilbao Montoya, Maria Pilar (Cranfield University, 2006)
Gastrointestinal symptoms have been observed to be present very often in autistic children. These symptoms are very similar to those observed in Irritable Bowel Syndrome (IBS). An investigation to investigate whether there is a similar cause for autism as well as IBS was done. Methods for the analysis of breath VOCs and urine organic acids were developed to be applied afterwards in the research of biomarkers of autism and IBS. Bacterial metabolites in urine and breath were identified by restricting the diets of healthy volunteers to each of two enteral feeds. The way enteral feeds work in the treatment of Crohn’s disease (CD) was investigated. Enteral feeds work by reducing bacterial activity in the gut, measurably reducing their metabolic products. The urine of IBS patients was analysed and bacterial compounds investigated. Some gastrointestinal symptoms are frequently misdiagnosed as IBS. According to the symptoms and treatment that is successful for these different groups of patients three subgroups can be made: “retention and overflow”, “musculoskeletal” and “abnormal fermentation” IBS. When the urine of these subgroups was observed, different biomarkers for the various subgroups could be identified. Patients with abnormal fermentation IBS have increased bacterial products in urine, suggesting an increase in bacterial activity in the colon. These biomarkers decreased after an exclusion or fibre-free diet and symptoms improved. In a further study, potential biomarkers for autism were identified. The origin of the majority of these compounds is unknown, although some of them are of known bacterial origin. A conclusion of this is that autistic children may exhibit abnormal fermentation since GI symptoms manifest at almost the same time as the autistic behavioural symptoms start and may be present from birth. Autistic children share many symptoms with IBS patients, although the biomarkers are different, showing that the GI symptoms observed in autistic children are not IBS in the children studied. More research needs to be done to determine the origin of the autism biomarkers discovered in urine.